The effect of six months of Topiramate supplementation use for weight loss on ambulatory blood pressure in abdominally obese males - Rideout, Rob (University of Ottawa (Canada), 2006)
Objective. To examine the effect of six months of Topiramate (TPM) supplementation use for weight loss on ambulatory blood pressure (ABP) in abdominally obese males. Methods. Sixty-eight abdominally obese males (Waist circumference >100 cm) with a BMI >27 and < 35 kg/m2 were assigned to the TPM or placebo group using a randomized pretest-posttest control group design with no behavioral modification. This was followed by a 12-week titration period and a 12-week stabilization period with a dosage up to 400 mg/d. Ambulatory blood pressure was monitored at baseline and at six months using the Spacelabs Medical Model 90207-31. Results. Topiramate supplementation group showed a significant decrease in systolic (5.2 +/- 9.79; p=0.006, -4.6 +/- 10.90; p=0.011 and -6.9 +/- 8.31; 0.003 mmHg) and diastolic (-3.7 +/- 6.13; p =0.006, -3.3 +/- 7.08; p=0.033 and -4.3 +/- 7.13; p=0.006 mmHg) 24-hr, daytime and nighttime ABP respectively. However, after performing an ANCOVA to control for the significant weight loss observed in the TPM supplementation group (-3.19 +/- 5.72 kg; p=0.006), systolic/diastolic 24-hr (p=0.233/0.147), daytime, (p=0.313/0.276) and nighttime (p= 0.108/0.187) changes in ABP were similar between the TPM and placebo group. Furthermore, change in systolic 24-hr ABP was significantly correlated to changes in % body fat (r=0.54; p=0.025), body fat mass (r=0.51; p=0.039) and total abdominal adipose tissue (r=0.46; p=0.043), whereas change in diastolic 24-hr ABP was significantly correlated to changes in total abdominal adipose tissue (c=0.51; p=0.043). Change in visceral adipose tissue (VAT) was not significantly related to changes in systolic/diastolic ABP (r=0.46/0.41; p=0.075/0.113) respectively. Discussion. These results suggest that the reduction in ABP observed in the TPM is mainly secondary to the reduction in body weight, especially the reduction in fat mass and total abdominal adipose tissue and not by the mechanistic abilities of the drug.
Keywords: Health Sciences, Recreation.; Biology, Physiology.